Regulations on Diversion in the Settlement of Children in Conflict with the Law: A Comparative Analysis of Positive Law and Islamic Criminal Law - Lubis, Suci Dini; Lubis, Syaddan Dintara (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2024)
Children who commit crimes must have their rights protected to ensure their survival and well-being. This study aims to apply diversion regulations in resolving cases of children in conflict with the law at the Women and Children's Services Unit of the Criminal Investigation Department in the Labuhanbatu Police Department to ensure the provision of restorative justice. This empirical legal study collected data through interviews with the Labuhanbatu Police Department. Findings indicate that diversion regulations are detailed in Law No. 11 of 2012 concerning the Juvenile Criminal Justice System. According to Islamic criminal law, if a child commits a crime, the punishment should be educational and involve al-shulhu (reconciliation). While diversion is carried out with a restorative justice approach, many juvenile offenses are not entirely diverted and are often processed further in the legal system. The practice of reconciliation for juvenile crimes in Labuhanbatu involves the upah-upah ceremony, which aligns with the concept of al-shulhu. Factors that prevent juvenile offenses from being resolved through diversion include cases of theft, embezzlement, and assault. This study recommends that diversion be mandatory for juvenile offenders at the stages of investigation, prosecution, and trial to resolve juvenile criminal cases